Avaliação de fundos como instrumentos de universalização dos serviços de saneamento: aplicação para o estado de Minas Gerais - Vitor Carvalho Queiroz (2016)
This paper evaluated two funding alternatives aiming at enabling the universalization of the water supply system and sanitary sewage. The first alternative consists of an analyses of instituting a State Sanitary Fund, based on the Special Public Fund concept and structured according to The Complementary State Law number 91, 2006. The first step was to estimate the resources deficit by the difference between the need and the capacity to carry out the investments. The need for investments was estimated through the model used by Plansab, where values had been projected for different universalization horizons: 2022, 2028 and 2033, and the capacity was determined from the recent history of carried out investments. Consequently, a deficit for each universalization horizon was found. The State Fund having been established, three sources were determined for its funding: part from the suppliers revenue; interest over the equity capital distributed to the State; and State budget. For eachsource, potential values destined to the fund were calculated, and then compositions among the three sources were simulated. An organizational structure was suggested, based on the existing legislation about the subject, as well as investment lines according to the assesseddemands up to the universalization, and afterwards, the criteria to be met to access each of these lines, were defined. The second fund is called regulatory and is based on tariff mechanisms used by the Arsae-MG. In this fund proposal, the possibility of using these tariff mechanisms for the regional service supplier of Minas Gerais State, The Copasa, was evaluated. The deficit was calculated by the same means as done for the State Fund. After this, the tariff increase to enable the universalization for each horizon was determined. The conclusion was that a State Fund is a fairer alternative, for its state coverage and for the redistributive nature of its funding sources. On the other hand, it is important to highlight that these kind of funding are susceptible to suffer deviations from their purposes, besides having a more complex implementation process. Considering these aspects, for being internal to the supplier, the Regulatory Fund has as its advantage, the greater possibility to achieve its purpose, especially by the regulator monitoring which hinders deviations of the funding aims. The weight in favor and against these considerations of the two proposed funding models, was that both instruments can help the so desired universalization of the water supply system and sanitary sewage.